2013
DOI: 10.1021/ja408512q
|View full text |Cite
|
Sign up to set email alerts
|

Redox-Induced Ion Pairing of Anionic Surfactants with Ferrocene-Terminated Self-Assembled Monolayers: Faradaic Electrochemistry and Surfactant Aggregation at the Monolayer/Liquid Interface

Abstract: Oxidoreduction of self-assembled monolayers (SAMs) of ferrocenyldodecanethiolate on gold in aqueous solutions of surface-active sodium n-alkyl sulfates (NaCnSO4) of 6, 8, 10, and 12 carbons is investigated by cyclic voltammetry and surface plasmon resonance. The effects of surfactant micellization and alkyl chain length on the redox response of the surface-tethered ferrocenes are examined. The SAM redox electrochemistry is sensitive to the surfactant aggregation state in solution. The nonideal behavior of the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

8
60
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 34 publications
(68 citation statements)
references
References 54 publications
8
60
0
Order By: Relevance
“…It was found previously that ferrocene moieties embedded in thicker organic films or farther away from electrode surfaces were more difficult to oxidize, resulting in higher E 0 values. 35,36 In our case, with a uniform spatial distribution of ferrocene sites throughout the polymer film (as evidenced by EDS), a thicker film may have led to a larger population of ferrocene moieties that were either buried more deeply in an organic PPY environment or were located farther away from the conductive surfaces (either CC or CNT); hence a thicker polymer film should result in a higher ensemble-averaged E 0 value. The thickness of a polymer film with uniformly distributed redox centers can be inferred from the slope (S iv ) of a ln(CV peak current)-ln(scan rate) plot obtained with a redox polymer electrode (RPE) model to simulate current responses (Section S4,ESI †).…”
Section: Simultaneous Enhancement Of Energetic Efficiency and Separatmentioning
confidence: 71%
“…It was found previously that ferrocene moieties embedded in thicker organic films or farther away from electrode surfaces were more difficult to oxidize, resulting in higher E 0 values. 35,36 In our case, with a uniform spatial distribution of ferrocene sites throughout the polymer film (as evidenced by EDS), a thicker film may have led to a larger population of ferrocene moieties that were either buried more deeply in an organic PPY environment or were located farther away from the conductive surfaces (either CC or CNT); hence a thicker polymer film should result in a higher ensemble-averaged E 0 value. The thickness of a polymer film with uniformly distributed redox centers can be inferred from the slope (S iv ) of a ln(CV peak current)-ln(scan rate) plot obtained with a redox polymer electrode (RPE) model to simulate current responses (Section S4,ESI †).…”
Section: Simultaneous Enhancement Of Energetic Efficiency and Separatmentioning
confidence: 71%
“…In this regard, we have investigated the redox-controlled association of surface-active sodium n-alkyl sulfates (NaC n SO 4 ) to SAMs of ferrocenyldodecanethiolate on gold (FcC 12 SAu, Scheme 1) and shown the feasibility of using the electrochemically induced pairing of counterions with surface-tethered redox moieties to drive the interfacial aggregation of ionic surfactants and surfactant-like molecules via an electrical stimulus. 6 Oxidation of the SAM-bound ferrocene (Fc) to ferrocenium (Fc + ) involves coupled electron-transfer and ion-pairing reactions: 3 …”
Section: ■ Introductionmentioning
confidence: 99%
“…An earlier investigation focused on the effects of the micellization of NaC n SO 4 in aqueous solution and surfactant chain length (6,8,10, and 12 carbons) on the redox electrochemistry of FcC 12 SAu SAMs. 6 We demonstrated that alkyl sulfate anions pair with SAM-bound ferroceniums and E°′ shifts to lower potential with increasing chain length.…”
Section: ■ Introductionmentioning
confidence: 99%
“…G. W. Gokel has reported the first example of vesicle formation from redox-switched hydrophobic ferrocene derivatives [21], and sonication-induced redox-switched vesicles formed by ferrocene derivatives upon oxidation [22]. With respect to surfactant, control of viscoelasticity using redox reaction [23], and redox-induced ion pairing of anionic surfactants [24] is also investigated. By using ferrocenoyl phenylalanine, Zhang Y. et al present a supramolecular hydrogel that exhibit sharp phase transitions in response to a series of different stimuli, including redox, guest-host interactions, and pH changes [25].…”
Section: Introductionmentioning
confidence: 99%